Regional Hip Hop and the Seoul Metropole: A Case Study of Underground Hip Hop in Gwangju - Farooqi, Amos (Journal of World Popular Music, 2021)
Advances in music technologies over the past two and a half decades have effectively democratized the production and distribution of music and de-agglomerated music industries in much of the developed world. Artists are no longer pressured to move to centres of musical agglomeration to further their careers and can now grow their profile while remaining in their respective localities. However, this phenomenon has not taken hold in the Korean music industry, which remains hyper-agglomerated in Seoul. Hip hop artists in Korea continue to cluster in the capital, while hip hop scenes in provincial cities are in a constant state of flux. This study examines the current state of provincial hip hop scenes through the case study of Gwangju, where interviews with local hip hop artists and participant observation was conducted between 2016 and 2019. This article argues that the concentration of commercial, political, media and educational institutions in Seoul forces ambitions of moving to the capital city upon provincial youths from an early age and pushes a Seoul-centric culture that weakens their bonds to their respective localities. Artists and crews in provincial cities are thus largely ignored by local audiences forcing them to move to the capital in search of success, which in turn weakens their respective local scenes.